Academic policies and conflicts of knowledge: challenges in the periphery - Palermo, Zulma (2016)
This article offers an analysis in the form of a case study, of the state of a University characterized by the author as in the periphery with regards to the current capitalist project. It intends to make evident the strategies of a spectral design -under the generalized appearance of a democratic, globalized equality-that maintains and deepens differences. Such design, academic as well as economic in nature, resorts in the end to a deontology that collaborates in making concrete the transformations looked for.